Populism - what next? A first look at populist walking-stick economies - Christopher Ball; Andreas Freytag; Miriam Kautz (Friedrich Schiller University Jena, 2019)
The recent rise in populist governments has led to much work on the question "why now?". Our work takes the next logical step by asking "what next?". That is, given populists in power, what should we expect to be the economic consequences of populist regimes. To answer this, we characterize populist economic policies and argue that they generate an inverted J-curve effect, which we term a "walking stick" effect, in macro-level data, specifically GDP and inflation. To test this claim, we construct a unique data set on 13 Latin American countries from 1976 to 2012 and incorporate more modern and nuanced definitions of populism. Our contribution is both to test the walking stick claim and to present a novel dataset for studying the economic effects of populism. We find compelling evidence for our walking stick hypothesis in both GDP per capita and inflation, suggesting that the answer to "what next" is that we will see on average short-run booms followed by declines under populist regimes.
Keywords: E39; E60; H11; N16; 330; Populism; Latin America; Business Cycle; Political Economy